Characterization of primary mouse hepatocyte spheroids as a model system to support investigations of drug-induced liver injury. (February 2021) - Nautiyal, Manisha; Qasem, Rani J.; Fallon, John K.; Wolf, Kristina K.; Liu, Jingli; Dixon, Darlene; Smith, Philip C.; Mosedale, Merrie
Abstract: Primary mouse hepatocytes isolated from genetically defined and/or diverse lines and disease models are a valuable resource for studying the impact of genetic and environmental factors on drug response and disease. However, standard monolayer cultures result in a rapid decline in mouse hepatocyte viability and functionality. Therefore, we evaluated 3D spheroid methodology for long-term culture of primary mouse hepatocytes, initially to support investigations of drug-induced liver injury (DILI). Primary hepatocytes isolated from male and female C57BL/6J mice were used to generate spheroids by spontaneous self-aggregation in ultra-low attachment plates. Spheroids with well-defined perimeters were observed within 5 days after seeding and retained morphology, ATP, and albumin levels for an additional 2 weeks in culture. Global microarray profiling and quantitative targeted proteomics assessing 10 important drug metabolizing enzymes and transporters demonstrated maintenance of mRNA and protein levels in spheroids over time. Activities for 5 major P450 enzymes were also stable and comparable to activities previously reported for human hepatocyte spheroids. Time- and concentration-dependent decreases in ATP and albumin were observed in response to the DILI-causing drugs acetaminophen, fialuridine, AMG-009, and tolvaptan. Collectively, our results demonstrate successful long-term culture of mouse hepatocytes as spheroids and their utility to support investigations of DILI. Highlights: 3D spheroids were generated from primary mouse hepatocytes in ULA plates Morphology, ATP, and albumin levels are stable for 2 weeks post spheroid formation Global mRNA profile, DMET protein level, and P450 enzyme activities are also stable Time- and concentration-dependent toxicity responses to DILI drugs were observed